THE ROLE OF COMPENSATION AND JOB SATISFACTION TOWARDS THE PERFORMANCE OF CIVIL SERVANTS THROUGH MOTIVATION AS MEDIATING VARIABLE AT DIRECTORATE OF AIRWORTHINESS AND AIRCRAFT OPERATIONS DIRECTORATE GENERAL OF CIVIL AVIATION THE MINISTRY OF TRANSPORTATION - Haris Hermawan Effendi; Chaerudin Chaerudin (Dinasti International Journal of Education Management And Social Science, 2021)
This research intend to reveal the impact of compensation and job satisfaction towards the performance of Civil Servants (PNS) at the Directorate of Airworthiness and Aircraft Operations (DKPPU), Directorate General of Civil Aviation at the Ministry of Transportation of the Republic of Indonesia through motivation as a mediating variable. The type of this research was included in quantitative research. The analytical method used the Structural Equation Modeling (SEM) by SmartPLS version 3.3.2. The total of a respondents who were sampled in this research were 70 DKPPU civil servants. The results explained that the compensation has a positive and significant influence on motivation, job satisfaction has a positive and significant influence on motivation, compensation has a positive and significant influence on performance, job satisfaction has a negative and insignificant affect towards performance, motivation has a positive and significant affect towards performance, compensation has a positive influence and significant on performance through motivation as a mediating variable, job satisfaction has a positive and significant influence on performance through motivation as a mediating variable.